Hadis-hadis dalam Kitab Durrat al-Nāṣiḥīn - Ahmad Lutfi Fathullah (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2008)
One of the traditions in the Muslim community is reading or studying the Kitab Kuning (classical Islamic texts). There are quite a variety of Kitab Kuning that are read in pesantren (Islamic boarding schools) or study groups, one of which is the book Durrat al-Nāṣiḥīn. This text is a summary of the author’s dissertation at Universiti Kebangsaan Malaysia (UKM) titled A Study of Hadith in the Book Durrat al-Nāṣiḥīn.